Controlling a Robotic Cell by Dynamic Rule Displacing: A Simulation Study - LEE, Shyanglin (Institutional Knowledge at Singapore Management University, 1990)
The main purpose of a Flexible Manufacturing System (FMS) is simultaneously to process parts with small to medium lot sizes and high varieties. The rule despatching problem in a Flexible Manufacturing Cell (FMC) is examined using a simulation model. This is based on an algorithm for dynamically selecting the best despatching rule according to the current system status. Comparison between simulation runs with and without dynamic rule despatching shows that the proposed algorithm gives a better overall performance.